Entrepreneurial Competencies in Graduate Students from Mexico: A Gender Perspective - Díaz Gómez, Eduardo Raúl (My University, 2022)
Mexico faces a gender gap in opportunity entrepreneurship. Part of the problem is themasculine approach to business education in graduate programs. This research uses data from 173 female and male graduate students to compare self-efficacy levels in entrepreneurship and leadership. The data were collected under a cross-sectional, survey research design. Findings suggest that there were no statistically significant differences between females and males in five entrepreneurship and two leadership dimensions. Statistically significant differences were identified in one entrepreneurship dimension: initiating relationships with investors. A key takeaway is that females undervalue their ability to secure funds for entrepreneurial purposes. RESUMEN México enfrenta una brecha de género en el emprendimiento de oportunidad. Parte del problema es el enfoque masculino de la educación empresarial en los programas de posgrado. Esta investigación utiliza datos de 173 estudiantes graduados femeninos y masculinos para comparar los niveles de autoeficacia en el espíritu empresarial y el liderazgo. La recolección de datos se realizó bajo un diseño de investigación transversal tipo encuesta. Los hallazgos sugieren que no hubo diferencias estadísticamente significativas entre mujeres y hombres en cinco dimensiones de emprendimiento y dos de liderazgo. Se identificaron diferencias estadísticamente significativas en una dimensión del emprendimiento: iniciar relaciones con inversionistas. Una conclusión clave es que las mujeres subestiman su capacidad para obtener fondos con fines empresariales.
Journal of International Women´s Estudies
Keywords: Self-efficacy; Opportunity Entrepreneurship; Gender; Campus Tijuana